Rancang Bangun Poltekom Electric Car Sebagai Modul Pembelajaran Teknik Mekatronika - Bintarto, Redi; Kusyairi, Imam (ROTOR, 2013)
POLTEKOM Electric Car is one of POLTEKOM effort to help the government programs in the development of electric cars . Many problems of electric cars for example in high cost and difficulties to finding spare parts into several constraints of the college to make an electric car . For this study researcher tried to designed and built an cheap electric cars which is capable of being used for transportation vehicle, both for moving people and goods with a certain capacity . To prove the target of this research purpose, we perform the strength of the chassis test , acceleration test , braking test and climbs test . By the testing, it is known that POLTEKOM Electric Car Able to move the maximum load of 200kg . Capable of driving a maximum of 35km/jam on flat road . Being able to climb the terrain with a slope of 15 degrees and is able to ride off after braking at a distance of 1 meter . By the datas that we collect during the test, it was analised and concluded that POLTEKOM Electric Car has been able to be used as human and material handling which can then be used as a learning module in mechatronic engineering . Keywords: electric car, material and human handling